Sustainability in the hospitality industry principles of sustainable operations - Legrand, Willy; Sloan, Philip; Chen, Joseph S. (Routledge, 2017)
"Sustainability in the Hospitality Industry, Third Edition, is the only book available to introduce students to economic, environmental and socially sustainable issues specifically facing the industry as well as exploring ideas, solutions and strategies of how to manage operations in a sustainable way."--Provided by publisher.